ANALISA MARKET OVERREACTION PADA SAHAM LQ 45 DI BURSA EFEK INDONESIA (Fokus Ekonomi, 2010)
The issue of this research is whether there is market overreaction in Indonesia Stock Exchange in the period 2008-2009. The aim of this research are to study and analyze whether there is overreaction in Indonesia Stock Exchange. The overreaction hypothesis is a manifestation of the inefficiency of the market (De Bondt and Thaler, 1985). Research on market overreaction used a sample of 20 shares in the company's listed at LQ-45. The result of this research are (1) in the winner portfolio return reversal does not occur in the test period, (2) in the loser portfolio return reversal occurred in the test period and (3) winners and losers portfolio do not show the different average abnormal return significantly. From the analysis, we can concluded return reversal only occurs in loser portfolio and the return reversal does not occur in the winner portfolio. Thus the research indicates only loser anomaly, this is caused by an overreaction to the bad news. The implication of this research is investors can use the contrarian strategy (buy low, sell high) to get abnormal return.